PERIPHERAL BLOOD-BASED POLYMERASE CHAIN REACTION IN DIAGNOSIS OF PULMONARY TUBERCULOSIS - Khan, Mumtaz Ahmad; Mirza, Sajjad Hussain; Abbasi, Shahid Ahmed; Butt, Tariq; Anwar, Masood (Journal of Ayub Medical College Abbottabad, 2006)
Background. The rapid diagnosis of infectious diseases, particularly those that represent a public health problem, like tuberculosis, is a challenging problem. By using nucleic acid amplification techniques like PCR, one may be able to diagnose, the disease on the day of arrival of specimen in the laboratory. For diagnosis of tuberculosis by direct methods like PCR, specimens from site of infection are required. In certain cases it is difficult to get the specimens from site of infection and in such situations; some researchers have tried to detect the DNA of Mycobacterium tuberculosis complex from blood of these patients. The purposive of this study is to determine the diagnostic efficacy of peripheral blood-based polymerase chain reaction for diagnosis of pulmonary tuberculosis. Methods. This was a simple descriptive study, carried out in Department of Microbiology, Armed Forces Institute of Pathology, Rawalpindi from Jan 2004 to Dec 2004. Sputum and blood samples were collected from 96 suspected patients of pulmonary tuberculosis. Sputum samples processed for ZN staining and AFB culture (gold standard) and blood samples processed for PCR. Results. Out of 96 cases, 60 (62.5%) were culture positive. PCR was positive in 14 (14.5%). AFB smear positive were 34 (35.4%). The overall sensitivity and specificity of the PCR assay was 20% and 94.4% respectively and the positive and negative predictive values were 85.71% and 41.46% respectively. The overall efficiency of the test was 47.91%. Conclusion. Due to low sensitivity; a negative PCR assay does not rule the disease. However, this test may be helpful in cases where specimens from the site of infection are not available. Key Words: PCR, peripheral blood, pulmonary tuberculosis